The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1055/s-0034-1544115
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure in a Riverside Amazon Population, Brazil: A Study of the Ototoxicity of Methylmercury

Abstract: Introduction Mercury poisoning causes hearing loss in humans and animals. Acute and long-term exposures produce irreversible peripheral and central auditory system damage, and mercury in its various forms of presentation in the environment is ototoxic. Objective We investigated the otoacoustic emissions responses in a riverside population exposed to environmental mercury by analyzing the inhibitory effect of the medial olivocochlear system (MOCS) on transient otoacoustic emissions (TEOAE). Methods The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…According to the year of publication, the articles were published as follows: three in 1998 [ 16 , 17 , 18 ], two in 1999 [ 19 , 20 ], three in 2000 [ 21 , 22 , 23 ], two in 2001 [ 24 , 25 ], one in 2002 [ 26 ], two in 2003 [ 27 , 28 ], four in 2005 [ 29 , 30 , 31 , 32 ], three in 2006 [ 33 , 34 , 35 ], two in 2007 [ 36 , 37 ], one in 2008 [ 38 ], one in 2009 [ 39 ], two in 2010 [ 40 , 41 ], three in 2012 [ 42 , 43 , 44 ], one in 2013 [ 45 ], one in 2014 [ 46 ], three in 2015 [ 47 , 48 , 49 ] and two in 2016 [ 50 , 51 ]. Most of the studies (61%) were performed exclusively by Brazilians Institution [ 16 , 18 , 20 , 21 , 22 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 37 , 41 , 42 , 43 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the year of publication, the articles were published as follows: three in 1998 [ 16 , 17 , 18 ], two in 1999 [ 19 , 20 ], three in 2000 [ 21 , 22 , 23 ], two in 2001 [ 24 , 25 ], one in 2002 [ 26 ], two in 2003 [ 27 , 28 ], four in 2005 [ 29 , 30 , 31 , 32 ], three in 2006 [ 33 , 34 , 35 ], two in 2007 [ 36 , 37 ], one in 2008 [ 38 ], one in 2009 [ 39 ], two in 2010 [ 40 , 41 ], three in 2012 [ 42 , 43 , 44 ], one in 2013 [ 45 ], one in 2014 [ 46 ], three in 2015 [ 47 , 48 , 49 ] and two in 2016 [ 50 , 51 ]. Most of the studies (61%) were performed exclusively by Brazilians Institution [ 16 , 18 , 20 , 21 , 22 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 37 , 41 , 42 , 43 ,…”
Section: Resultsmentioning
confidence: 99%
“…There was a predominance of studies that were performed in the State of Pará (47%) [ 22 , 23 , 25 , 26 , 27 , 29 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 43 , 45 , 47 , 48 ]. Some studies had been performed in the State of Amazonas (22%) [ 17 , 19 , 24 , 30 , 33 , 41 , 44 , 49 ], Rondônia (14%) [ 18 , 28 , 46 , 50 , 51 ], Mato Grosso (8%) [ 21 , 31 , 32 ] and Amapá (3%) [ 20 ]. Two studies were performed using samples from populations from two different States: Pará and Rondônia (3%) [ 16 ] and Rondônia and Amazonas (3%) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The general population is primarily exposed to heavy metal ions via food [ 23 ]. For instance, fishes are the major source of methylmercury and dental amalgam [ 19 ]. However, the general population does not face a significant health risk from methylmercury, although certain groups, especially with regional high fish consumption, may attain blood levels associated with a low risk of neurodegenerative abnormalities or damage [ 5 , 13 , 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…No correlation between mercury levels and age was found supporting the fact that age may not be an influencing factor for mercury exposure in adults. Accordingly, previous works already demonstrated no association between both factors in adults ( Hoshino et al, 2015 ; Arrifano et al, 2018b ), although it can be observed in children ( Barbosa et al, 1998 ; Pinheiro et al, 2007 ; Marques et al, 2016 ). Moreover, it is also relatively frequent to find higher mercury levels in men than those in women, usually attributed to a higher consumption of fish ( Dolbec et al, 2000 ; Fillion et al, 2006 ; Passos et al, 2007 ; Ashe, 2012 ), as we detected in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Worryingly, several studies have demonstrated high mercury content in hair of some riverine populations in Amazon ( Berzas Nevado et al, 2010 ; Marques et al, 2013 ; Hacon et al, 2014 ; Hoshino et al, 2015 ; Arrifano et al, 2018b ). These communities are exposed mainly to methylmercury (MeHg) through consumption of contaminated fish ( Berzas Nevado et al, 2010 ; Rodriguez Martin-Doimeadios et al, 2014 ; Arrifano et al, 2018b ), as other vulnerable populations throughout the world ( Drescher et al, 2014 ; Strain et al, 2015 ; Langeland et al, 2017 ; Salazar-Camacho et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%